STUDI PENGGUNAAN DEKSAMETASON PADA PASIEN COVID-19 DERAJAT BERAT DENGAN KOMORBID DIABETES MELLITUS - Hasmono, Didik; As-Shiddiq, Hasbi; Insyirah Idris, Anissah; Agriawan Sudirman; Hartono, Ruddy; Subhan, Mohammad (Jurnal Kesehatan, 2023)
Administration of Dexamethasone in patients with diabetes needs attention because corticosteroids can increase blood glucose concentrations. Therefore, this study aims to determine the effectiveness of using Dexamethasone in patients with severe COVID-19 and how to regulate blood glucose in patients with severe COVID-19 in patients with comorbid Diabetes Mellitus. Inclusion criteria for severe COVID-19 patients with comorbid Diabetes Mellitus who use Dexamethasone and therapy groups and receive insulin therapy with or without OAD in inpatient installations. The sample data obtained from the patient's medical records were 27 patients who met the inclusion and exclusion criteria consisting of 70% male and 30% female. Dexamethasone dose of 1 x 6 mg iv mostly uses combination therapy A, the duration of administration is 8 days, and has an average length of stay of 13 days. The shortest average length of hospitalization was 12 days for patients receiving dexamethasone with therapy C for 10 days, while therapy B for 5 days had an average hospitalization of 14 days. Administration of Dexamethasone dose of 1 x 6 mg iv is effective in severe COVID-19 patients with comorbid Diabetes Mellitus based on the length of hospitalization, respectively 13 days, 14 days, and 12 days with an improvement in the clinical condition of oxygen saturation by 91%, 100%, 100%; RT-PCR/Rapid Ag became negative 74%, 100%, 100%; improvement of chest x-ray results, namely 83%, 33%, 100%. The effect of glucocorticoid dexamethasone in comorbid Diabetes Mellitus patients is regulated by administering long-acting insulin, rapid-acting insulin, and oral anti-diabetic.